2020
DOI: 10.1186/s12934-020-01391-4
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced multi-stress tolerance and glucose utilization of Saccharomyces cerevisiae by overexpression of the SNF1 gene and varied beta isoform of Snf1 dominates in stresses

Abstract: Background The Saccharomyces cerevisiae Snf1 complex is a member of the AMP-activated protein kinase family and plays an important role in response to environmental stress. The α catalytic subunit Snf1 regulates the activity of the protein kinase, while the β regulatory subunits Sip1/Sip2/Gal83 specify substrate preferences and stress response capacities of Snf1. In this study, we aim to investigate the effects of SNF1 overexpression on the cell tolerance and glucose consumption of S. cerevisiae in high glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 49 publications
1
11
2
Order By: Relevance
“…The change of each amino acid was not the same in SNF1 overexpression under different conditions, such as that in freezing and non-freezing in this work and that in high glucose, ethanol, and heat shock stresses of our previous study [33]. In addition, Nicastro et al [42] showed that Snf1 inhibited the biosynthesis of amino acids in amino acid-rich condition.…”
Section: Glycerophospholipid Metabolism Cho2 Psd2 Spo14 Ale1 Gpd2contrasting
confidence: 54%
See 1 more Smart Citation
“…The change of each amino acid was not the same in SNF1 overexpression under different conditions, such as that in freezing and non-freezing in this work and that in high glucose, ethanol, and heat shock stresses of our previous study [33]. In addition, Nicastro et al [42] showed that Snf1 inhibited the biosynthesis of amino acids in amino acid-rich condition.…”
Section: Glycerophospholipid Metabolism Cho2 Psd2 Spo14 Ale1 Gpd2contrasting
confidence: 54%
“…Related studies have shown that the fermentation ability of proline-accumulating baker’s yeast in frozen dough is higher than that of the wild strain [ 31 ]. The content of glycerol, a well-known metabolite as a cell cryoprotectant [ 32 , 33 ], was significantly upregulated in the transformant ABY+S. In addition, three substances in the differential metabolites were related to cell membrane components: upregulated palmitic acid and downregulated sn-1LysoPC (16:0) and sn-1LysoPE (18:1).…”
Section: Resultsmentioning
confidence: 99%
“…Currently, research goals in developing the biotechnological application of oleaginous microorganisms focus on enhancing target PUFA yield and reducing the production cost . For heterotrophic oleaginous microorganisms, the glucose utilization rate is a determinant factor that affects fermentation cost and final lipid yield . To enhance glucose utilization, genes involved in glucose transportation and metabolism have been modified to strengthen the allocation of carbon flux toward lipid synthesis. , In addition, some protein kinases with global regulatory roles also attract research interest. , Among them, the heterotrimeric sucrose nonfermentable protein kinase 1 (SNF1), homolog of mammal adenosine monophosphate-activated protein kinase (AMPK), is one of the well-known global regulators that plays a vital role in lipogenesis and cellular responses to nutrient levels.…”
Section: Introductionmentioning
confidence: 99%
“…7 For heterotrophic oleaginous microorganisms, the glucose utilization rate is a determinant factor that affects fermentation cost and final lipid yield. 8 To enhance glucose utilization, genes involved in glucose transportation and metabolism have been modified to strengthen the allocation of carbon flux toward lipid synthesis. 6,9 In addition, some protein kinases with global regulatory roles also attract research interest.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The Snf1 protein kinase is a complex that consists of an alpha catalytic subunit Snf1, a gamma regulatory subunit Snf4, and one of the three alternative beta regulatory subunits, namely, Sip1, Sip2, and Gal83 (Daniel and Carling, 2002;García-Salcedo et al, 2014;Meng et al, 2020). Snf1 activation requires at least two steps: First, Snf4 binds to the C-terminal regulatory domain of the catalytic subunit Snf1 to counteract the autoinhibition of Snf1, in which β regulatory subunits participate in the linkage of Snf1 and Snf4, and direct the subcellular localization of Snf1 (McCartney and Schmidt, 2001).…”
Section: Introductionmentioning
confidence: 99%